Effectiveness Use of the Jkn Mobile Application in Health Services at Gunung Tua General Hospital, North Padang Lawas - Tiasa Pohan; Mhd.Fadlillah Nasution; Johan Saputra (International Journal of Public Health Excellence (IJPHE), 2026)
Advances in information technology sometimes require people to keep up with the times. Currently, the use of information and communication technology is crucial for businesses and organizations to win the competition. This study aims to analyze the effectiveness of the use of the JKN mobile application in healthcare services at Gunung Tua General Hospital. This research method uses a qualitative research method with a descriptive approach. Data collection was conducted through in-depth interviews, observation, and documentation with informants determined using a purposive sampling technique. The results show that the use of the JKN Mobile application has a positive impact on healthcare services, particularly in accelerating the registration process and reducing patient queues. This application is considered to help with time efficiency and increase user comfort. It is recommended that BPJS Kesehatan and the hospital increase socialization and education activities regarding the use of the JKN Mobile application, both through print and digital media, as well as direct patient assistance. In addition, improvements in the quality of technical services, including system and network stability, need to be continuously carried out. The hospital is also expected to provide special staff to assist patients who experience difficulties in using the application